2009
DOI: 10.1111/j.1349-7006.2009.01281.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of BRAK / CXCL14 gene expression by gefitinib is associated with antitumor efficacy of the drug in head and neck squamous cell carcinoma

Abstract: Clinical efficacy of gefitinib (ZD1839, Iressa), which is an inhibitor specific for epidermal growth factor (EGF) receptor tyrosine kinase, has been shown in non-small-cell lung carcinoma patients with EGF receptor mutations, so these mutations are useful marker(s) to find a responder for the drug. Recent studies have shown that the EGF receptor gene mutation is rare in squamous cell carcinoma in the esophageal and head and neck regions. We previously reported that the expression of the chemokine BRAK/CXCL14 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 35 publications
4
57
0
Order By: Relevance
“…Consistent with the results reported by a number of previous tumor-related studies (23)(24)(25)(26)(27)(28), the present study detected that the expression levels of CXCL14 in colorectal carcinoma tissues were significantly lower than those in normal tissues. The current study did contradict the findings of Zeng et al (32), but was consistent with the results of Cao et al (33).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consistent with the results reported by a number of previous tumor-related studies (23)(24)(25)(26)(27)(28), the present study detected that the expression levels of CXCL14 in colorectal carcinoma tissues were significantly lower than those in normal tissues. The current study did contradict the findings of Zeng et al (32), but was consistent with the results of Cao et al (33).…”
Section: Discussionsupporting
confidence: 82%
“…The identification of CXCL14 led to clinical research into other diseases, including obesity (19,20), bacterial infections (21) and immune system disorders (22,23). In addition to breast cancer tissues, studies have demonstrated low or absent CXCL14 expression in other tissues, including lung cancer, head and neck squamous cell carcinoma, hepatocellular carcinoma and gastric cancer (23)(24)(25)(26)(27)(28). However, in prostate and pancreatic cancer, CXCL14 is generally expressed at a high level (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, introduction of small interference RNA expression-vector for BRAK into HSC-3 cells reduced both the expression levels of BRAK in HSC-3 cells and the antitumor efficacy of gefitinib in vivo. These data also indicate that BRAK expression is essential for tumor suppression in vivo (14). The same or a higher level of natural killer (NK) cell activity is present in SCID mice compared with wild-type C.B-17 mice (26); and BRAK/CXCL14 stimulates the migration of activated NK cells but does not affect the proliferation or cytotoxic activity of normal NK cells (21), suggesting that NK cells are partially responsible for BRAK/CXCL14-dependent tumor suppression and that the co-presence of a NK cell activator(s) is essential for tumor suppression.…”
mentioning
confidence: 67%
“…The expression is negatively regulated by the binding of epidermal growth factor (EGF) to its receptor (16); and when HNSCC cells are treated with gefitinib, an epidermal growth factor tyrosine kinase inhibitor, the expression of BRAK/CXCL14 protein increases under culture conditions (15). Interestingly, the oral administration of gefitinib significantly (P < 0.001) reduces the growth of tumor xenografts of 3 HN-SCC cell lines (HSC-2, HSC-3 and HSC-4) in female athymic nude mice, which reduction is accompanied by an increase in BRAK expression specifically in the tumor tissue; this tumor-suppressing effect of the drug is not observed in the case of BRAK non-expressing cells (15). Furthermore, the introduction of a vector expressing short hairpin RNA against BRAK reduces both the expression level of BRAK/CXCL14 in HSC-3 cells and the antitumor efficacy of gefitinib in vivo (15).…”
Section: Effects Of Expression Of Brak Protein By Tet-on Brak Hsc-2 Cmentioning
confidence: 99%